The Power of Expression of the Language Within the Advertising Message and The Current Linguistic Situation - Mitseva, Stoyanka (Research Papers, 2017)
The ever-changing dynamic communication environment where the advertising message exists, is characterized by having huge verbal potential whose key tools, relevant to specific advertisements, are also influenced by the contemporary language developments. On the other hand, the link between the community and its needs finds manifestation in the commercial advertising message (through the advertising strategies and tactics). Unlike the specialized business and commercial text which issubject to specific requirements and strictly regulated construction principles, the advertising message which reaches its audience via the media, is characterized by figurativeness and practicality. This can easily be confirmed by getting to the essence of the advertising discourse, where by discourse we mean the broad boundaries of conceptual thinking and elaboration on the topic of advertising. However, it is also a means of communication, i.e. it is usedto conduct social interaction, since it is an element of the market communication. It could be concluded that a discourse is a specific situation-related speech or text, created to impress us indirectly and motivate us to act (to become potentia/consumers).